IMPLEMENTATION AND TRIAL OF BASIC POWDER TO INCREASE FISHING RESULTS IN THE WATERS OF LHOK PAROY, ACEH BESAR - Muhammad; Syamsul Rizal; Zulfan; Syarifuddin; Zulkarnaini Jalil; Rizwan; Tasya Aspia (CV. Naskah Aceh, 2025)
Bubu is one type of fishing gear that operates passively on the bottom of the water. In general, bubu is classified as a catching device in the form of a cage or a closed room, where the fish that enter it cannot come out again. This dedication program aims to apply and test the bottom trap construction that is operated in the waters of Lhok Paroy, as well as evaluate its effectiveness in increasing the catch of local fishermen. This activity was carried out in July-August 2023, located in Paroy Village, Lhoong District, Aceh Besar Regency. The method used is a test method (experimental fishing) by operating a trap directly in the location. The result of the dedication shows that the construction of the trap used has a length of 1.5 m, a width of 1.0 m, and a height of 0.5 m, with a mesh size of 2 inches, additional weights tied to the rope of the branch, and a buoy as a marker of the presence of the trap . As many as 6 species of fish were identified in the catch of bubu, namely red snapper (Lutjanus malabaricus), grouper fish (Epinephelus coioides), chicken fish (Balistoides viridescens), pomace fish (Platax teira), gaga snapper (Lutjanus rivulatus), and treacherous fish (Lutjanus johnii). The total number of fish caught was 16 from 3 trips, with a total weight of 13,474 grams. This result shows that the application of this basic trap has the potential to increase the catch of fishermen in the waters of Lhok Paroy, Aceh Besar.